Exploring in the Ancient Urban Center of Samatata: Initial Documentation of Archaeological Discoveries in the Lalmai Hill Range, Cumilla, Bangladesh - Bakhtiar Uddin Badal; Sumaia Khatun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The study aimed to investigate the Lalmai Hill range in Cumilla, Bangladesh, which was the capital center of ancient Samatata, to uncover new archaeological sites. Over the years a total of 50 archaeological sites have been identified on the hills' flat tops and slopes through multiple phases of exploration conducted by the Archaeological Survey of India's Eastern Circle, the Department of Archaeology and Museums of Pakistan, and the Department of Archaeology under the cultural ministry of the Bangladesh Government. The archaeological sites discovered provide a captivating glimpse into the 7th to 8th century AD. This era is characterized by significant cultural and societal transformations, making it a compelling and pivotal period to explore. While most of these sites were discovered in the northern and middle parts of the Hill range, this study specifically focused on the southern part. Through several field surveys, a new archaeological site was discovered in the south zone of the Hill range. The findings revealed ancient bricks, wall structures, and potshards, indicating the presence of past human activities at the site. These findings provide insights into the historical and cultural significance of the region. Further exploration and excavation of this site and other potential areas within the Lalmai Hill range are warranted to enrich our understanding of the past culture and unearth other hidden treasures